2021
DOI: 10.1149/1945-7111/abdfe1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterisation of Gold Nanoparticles/Poly3,4-Ethylene-Dioxythiophene/Reduced-Graphene Oxide for Electrochemical Detection of Dopamine

Abstract: In this research, the electrochemical method was used as a tool with the newly proposed electrode to detect dopamine (DA) in the urine sample. Gold/Poly3,4-ethylene-dioxythiophene/reduced-graphene oxide (AuNPs/PEDOT/rGO) nanocomposite material was synthesised via the facile one-pot method. The presence of Au/PEDOT on the rGO sheet was investigated by Fourier Transform Infrared (FTIR) spectrometer, Scanning Electron Microscope (SEM) and Ultraviolet-visible (UV–vis) spectroscopy. The synthesised nanocomposite ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…According to theory, eqn (1) and (2) , if the peak interval Δ E is 59 mV, the ratio of peak currents is approximately 1, both parameters indicating that the process is an ideal reversible reaction. 38 Therefore AuNPs/PEDOT/CNTs/GCE has quasi-reversible property. Δ E = E pa − E pc | I pa / I pc | = 1 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to theory, eqn (1) and (2) , if the peak interval Δ E is 59 mV, the ratio of peak currents is approximately 1, both parameters indicating that the process is an ideal reversible reaction. 38 Therefore AuNPs/PEDOT/CNTs/GCE has quasi-reversible property. Δ E = E pa − E pc | I pa / I pc | = 1 …”
Section: Resultsmentioning
confidence: 99%
“…This may be related to the synergistic effect between gold nanoparticles, acidified carbon nanotubes and PEDOT. By studying the effect of different scan rates on the dopamine response, it was found that the redox peak current was proportional to the scan rate, and the characteristic peak potential did not change much, which indicated that the electron-transfer reaction of dopamine at the electrode surface is a diffusion-controlled process, 38 the reaction kinetics between the redox sites is stable ( Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Yet, defect-free graphene could not be synthesized in large scale due to the oxidation on the graphene surface. Reduced graphene oxide (rGO), a derivative recompense this hindrance with improved properties of larger active site at its surface [4]. Reduction of graphene makes the compound coexist in between graphene and graphene oxide (GO), in other words having the compound defect-less while retaining its unique properties [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…16,18 Using FSCV along with CFMEs provides for rapid analysis with a high degree of accuracy for representative biomolecule concentration changes in the brain. [18][19][20] This technique was used to detect monoamines in the brain such as dopamine 21 serotonin, 22,23 norepinephrine, 24 amino acids, [25][26][27] and others 28 Recently, it has been adapted for the measurement of DNA and 29 biomolecules 30 and the detection of hormones 31 and neurochemicals. 32 FSCV has also been used to detect analytes that foul such as melatonin in live mesenteric lymph node slices, further exemplifying the versatility of this technique.…”
mentioning
confidence: 99%